Creation of Punjabi WordNet and Punjabi Hindi Bilingual Dictionary - Rattan, Rekha (My University, 2011)
India is a multilingual country wherein people speak many different languages .Therefore a lot of work can be done in the fields of machine translation and cross lingual information processing. This acted as a motivation behind the building of IndoWordNet. IndoWordNet is a linked structure of WordNets of major Indian languages. Many Indian languages are using the expansion approach to develop their WordNets from the Hindi WordNet. Punjabi is the language of hundreds of millions of people in India, and is the religious language of all Punjabis around the world. Surprisingly little work has been done in the field of computerized language and lexical resources for this language. It is therefore worthy to build up a Punjabi lexical resource (WordNet) that can discover the richness of language Punjabi. This thesis consists of a brief overview of WordNet and its underlying main beliefs in different languages. This thesis describes our approach towards building a lexical resource in Punjabi language. Punjabi WordNet is being developed from Hindi WordNet using the expansion approach. An algorithm for creating Punjabi Hindi bilingual dictionary by using Punjabi WordNet has also been proposed in this thesis work. A methodology for development of a web application for Punjabi Hindi bilingual dictionary has also been discussed in this thesis.
M.E. (CSED)
Keywords: WordNet; Punjabi WordNet